Successful therapies for Alzheimer’s disease: why so many in animal models and none in humans? - Franco, Rafael; Cedazo-Minguez, Angel (Frontiers in Pharmacology, 2014)
Peering into the field of Alzheimer's disease (AD) the outsider realizes that many of the therapeutic strategies tested (in animal models) have been successful. One also may notice that there is a deficit in translational research, i.e. to take a successful drug in mice and translate it to the patient. Efforts are still focused on novel projects to expand the therapeutic arsenal to "cure mice". Scientific reasons behind so many successful strategies are not obvious. This article aims to review the current approaches to combat AD, and to open a debate on common mechanisms of cognitive enhancement and neuroprotection. In short, either the rodent models are not good and should be discontinued, or we should extract only the most useful information from those models. An example of a question that may be debated for the advancement in AD therapy is: In addition to reducing amyloid and tau pathologies, would it be necessary to boost synaptic strength and cognition? The debate would provide helpful information that could turn around the current negative output in generating effective drugs for patients. Furthermore, discovery of biomarkers in human body fluids, and a clear distinction between cognitive enhancers and disease modifying strategies, should be instrumental for advancing in anti-AD drug discovery.